Sustainable development in the shadow of climate change - Sťahel, Richard (Civitas: revista de Ciências Sociais, 2019)
Development plans at different levels – from local to global – aspire to eliminate poverty, famine, to make health care accessible, to create better access to education, to improve transportation, employment, and the quality of life, all within next decades. Yet, these plans collide with the reality of climate change, more precisely the Anthropocene, which already creates high-dimensional conflicts. These will only intensify within decades because climate change and other consequences of the environment global devastation lead to a real decrease of resources. These resources enable not only development but also an elementary reproduction of the essential preconditions of life. The current model of development has substantially contributed to the intensification of unequal accessibility to resources and existing conflicts have thus heightened and new ones have emerged. Water as an essential resource will cause new conflicts. Growing population, expansion of deserts and a sea level rise then increase conflicts for the land. Heat waves occur more often which strengthens conflicts for land suitable for human life, meaning that inhabitable areas are spreading. Therefore there is a need to re-evaluate the character and hierarchy of resources and their accessibility, and also concepts of development. The existing development of humankind has been done at the expense of others in many cases and mainly at the expense of the environment. The current situation raises a question of climate justice from both historical and systematic viewpoints. It opens a need to reformulate the concept of human rights from the perspective of their essential environmental preconditions and to define the status of environmental migrants.